The Evolution and Technical Landscape of Decentralized Finance: From DeFi to DeFi 2.0 - Likhit Mada, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive technical article explores the evolution and architectural landscape of Decentralized Finance (DeFi), examining its transformation from initial implementations to the more sophisticated DeFi 2.0 ecosystem. It investigates the fundamental technical components, including smart contract infrastructure, consensus mechanisms, and cross-chain interoperability solutions that form the backbone of modern DeFi systems. Through a detailed examination of Layer-2 scaling solutions, risk management protocols, and AI-driven analytics, the article highlights how DeFi aggregators are revolutionizing user interactions with decentralized protocols. It further delves into emerging technologies such as zero-knowledge proofs and quantum-resistant cryptography, while addressing critical challenges in security, scalability, and mainstream adoption. By examining both technical innovations and integration challenges, this article provides insights into how DeFi is reshaping traditional financial systems through decentralized protocols and smart contracts while emphasizing the importance of balancing innovation with security and regulatory compliance in the evolving blockchain landscape.
Keywords: Decentralized Finance; Layer-2 Scaling Solutions; Zero-Knowledge Proofs; Cross-chain Interoperability; Smart Contract Security